Peran Guru Agama Katolik dalam Pembinaan Iman Siswa di SD Negeri 045957 Suka - Din Oloan Sihotang; Ray Andika Perangin-angin; Ermina Waruwu (Publisher STPKat, 2025)
As a substitute for parents in school, the role of Catholic Religious Education (PAK) teachers is crucial in guiding and nurturing students to avoid behaviors that may lead them towards inappropriate social interactions. This research is significant to understand the role of Catholic Religious Education (PAK) teachers in shaping the faith of Catholic students at SD Negeri 045957 Suka, Kabupaten Karo. The research methodology employed is qualitative, involving observations, interviews, and document analysis. Data was collected through observing PAK teachers' activities, interviewing teachers, the school principal, other subject teachers, and students, as well as analyzing documents related to the Catholic religious curriculum. The research was conducted at SD Negeri 045957 Suka in the sixth grade over a period of three months. The findings indicate that the creative and in-depth teaching methods of PAK teachers are effective in strengthening students' faith through prayer, Bible teachings, and active participation in church worship. The results underscore the need for enhanced teacher training in deep teaching approaches and the integration of Catholic values into daily school activity.